2009
DOI: 10.1128/jvi.01256-09
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage-Mediated Toxin Gene Regulation in Clostridium difficile

Abstract: Clostridium difficile has been identified as the most important single identifiable cause of nosocomial antibiotic-associated diarrhea and colitis. Virulent strains of C. difficile produce two large protein toxins, toxin A and toxin B, which are involved in pathogenesis. In this study, we examined the effect of lysogeny by ⌽CD119 on C. difficile toxin production. Transcriptional analysis demonstrated a decrease in the expression of pathogenicity locus (PaLoc) genes tcdA, tcdB, tcdR, tcdE, and tcdC in ⌽CD119 ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
85
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 41 publications
5
85
0
Order By: Relevance
“…Previous reports have shown that toxin production in C. difficile can be affected by some prophages (14,18). In order to test whether CD38-2 could influence toxin production in C. difficile, we infected the host isolate CD274, which is a representative member of the hypervirulent strain BI/NAP1/027, to create lysogens.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have shown that toxin production in C. difficile can be affected by some prophages (14,18). In order to test whether CD38-2 could influence toxin production in C. difficile, we infected the host isolate CD274, which is a representative member of the hypervirulent strain BI/NAP1/027, to create lysogens.…”
Section: Resultsmentioning
confidence: 99%
“…So far, C. difficile phages have not been found to encode proven virulence factors or to convert nontoxigenic C. difficile isolates into toxin-producing lysogens (15,17,20,34). Nevertheless, two recent studies suggest that phages may somehow contribute to the regulation of toxin production in C. difficile (14,18), but the clear lack of data regarding phages of C. difficile makes it difficult to appreciate the real impact of prophages on C. difficile lifestyle and virulence.…”
mentioning
confidence: 99%
“…Few studies investigating gene expression in C. difficile have been performed (Gerber et al, 2008;Govind et al, 2009;Karlsson et al, 2008) and, as a result, little is known about the regulation of genes, virulence-related or otherwise. With respect to the binary toxin, Carter et al (2007) demonstrated expression of cdtA during the stationary growth phase and expression was significantly reduced in strains with a mutation in cdtR, a gene encoding a putative regulator.…”
Section: Introductionmentioning
confidence: 99%
“…35 In another example, a prophage repressor, RepR, of Clostridium difficile, a common causal agent of nosocomial infections of the intestine, has been found to bind the promoter region of the gene tcdR of the PaLoc pathogenicity island modulating toxin production. 36 In a different strategy that avoids host death, many of the prophage genomes in enterohaemorrhagic E. coli (EHEC) strains and other bacteria are found to be missing genes or have mutations in genes known to be essential for a bacteriophage to enter the lytic cycle and to be horizontally transferred. These bacteriophage remnants were assumed to have in fact lost their ability to be transferred between cells.…”
mentioning
confidence: 99%